Hemodynamic Effects of Oxytocin when Given as Bolus or Slow Intravenous Infusion During Cesarean Section (Journal of Enam Medical College, 2021)
Background: Oxytocin is a uterotonic drug with profound haemodynamic effects. The effects of oxytocin on women undergoing cesarean section include tachycardia, hypotension and decreased cardiac output. These can be sufficient to cause significant compromise in high risk patients.Objective: This study aims to find out a simple way to decrease these risks without compromising the therapeutic benefits such as decreasing bleeding after delivery and uterine contraction.Materials and Methods: We recruited 60 women undergoing cesarean section. The subjects were randomly divided into two groups, 30 subjects per group, randomly selected by blind envelope method. Group A: parturient received 5 IU bolus (approximately over 2 seconds). Group B: parturient received 5 IU oxytocin IV slow infusion (diluted with 10 mL distilled water) over 2 minutes.Results: A significant increase in heart rate and fall in blood pressure in the group where oxytocin was given IV bolus compared to the slow IV infusion group. There were no differences in the estimated blood loss and uterine contraction between the two groups.Conclusion: The haemodynamic changes are more marked in the IV bolus than the slow IV infusion of oxytocin. Slower injection of oxytocin can effectively minimize the cardiovascular side effects without compromising the therapeutic benefits.J Enam Med Col 2021; 11(2): 92-98